ARTIFICIAL INTELLIGENCE IN CONSTRUCTION AND LANDSCAPE DESIGN: APPLICATIONS IN PLANNING, SCHEDULING, AND ENGINEERING TO INCREASE EFFICIENCY - Яцюк, В. (SWorldJournal, 2026)
The construction and landscape industries face numerous challenges: from rising costs, frequent delays and low productivity to a number of issues related to the rational use of resources and compliance with environmental standards. This article reviews th